Enamel Resistance to Demineralisation around Orthodontic Brackets after CO2 Laser Irradiation: A Randomised Clinical Trial. (December 2018) - Raghis, Tuqa; Mahmoud, Ghiath; Abdullah, Ahmed; Hamadah, Omar
Objective: To evaluate the clinical effect of 10.6 µm CO2 laser irradiation on the formation of demineralised lesions (DLs) around orthodontic brackets. Design: A two-arm, split-mouth, randomised clinical trial (RCT). Setting: The Orthodontic Department, Faculty of Dentistry, Damascus University, Syria. Participants: Twenty-six patients with a total of 520 teeth were recruited into the trial. Method: Two reversed quadrants of the dental arches in each patient were randomly allocated to CO2 laser application around the orthodontic brackets. The other two quadrants received a control non-therapeutic light. There was blinding of both patients and assessors in the study. The primary outcome was the presence or absence of at least one new DL observed by clinical and photographic examinations. Secondary outcomes included the degree and area of DLs measured on digital images and DIAGNOdent assessment. Teeth were examined before bonding (T0), after bonding and laser irradiation (T1), after 1 month (T2), 2 months (T3) and 6 months (T4). Results: The presence of at least new DL was significantly lower in the laser group when observed at 2 and 6 months ( P  < .0001), the DLs degree and area were also significantly lower in the laser group at 2 and 6 months ( P  ≤ .005), and DIAGNOdent values were significantly lower in the laser group ( P  < .0001) at all observation times. Conclusions: Enamel irradiation with a CO2 laser (at the wavelength of 10.6 µm) has an inhibitory effect on DL formation during orthodontic treatments. Registration: The trial was registered at ClinicalTrials.gov, number NCT03114475.